Analysis of task allocation in distributed software development through a hybrid methodology of verbal decision analysis. Issue 7 (11th April 2017) - Simão Filho, Marum; Pinheiro, Plácido Rogério; Albuquerque, Adriano Bessa
Abstract: The management of distributed software development projects presents many challenges. One of them happens right at the start of the project and consists of the allocation of tasks between remote teams. When allocating a task to a site, the project manager takes into account several factors such as technical knowledge of staff and proximity to the client. The project manager usually takes this decision in a subjective way. The verbal decision analysis is an approach based on solving problems through multicriteria qualitative analysis, which means it considers the analysis of subjective criteria. This paper describes the application of verbal decision analysis methods ORdinal CLASSification and ZAPROS III‐i to classify and rank the most relevant factors that the project managers should take into account when allocating tasks in projects of distributed software development. Abstract : Working with distributed teams is an alternative increasingly present in large companies. However, the distribution brings many challenges, particularly concerning the allocation of tasks to remote teams. This paper describes the application of a hybrid methodology based on ORCLASS and ZAPROS III‐i methods of Verbal Decision Analysis, a Multi‐criteria Decision Analysis framework, to classify and rank order the most important factors that project managers should consider when allocating tasks to distributed teams in projects of distributed software development.